2022
DOI: 10.22159/ijpps.2022v14i2.43400
|View full text |Cite
|
Sign up to set email alerts
|

Opuntia Elatior Mill.–its Phytochemistry and Pharmacological Properties-a Review

Abstract: Opuntia elatior Mill. (OE) (Family Cactaceae), commonly recognized as Red Prickly pear, is a plant of varied nutritional and medicinal benefits. The species has been scrutinized for the composition and wide array of pharmacological activities. This review is attempted with an aim to document the updated status of OE with respect to its phytochemistry and pharmacological actions. The data is collected from the extensive review of literatures from scientific articles, dissertations and books available on various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to several studies (Longo et al, 2007;Dahmoune et al, 2014), this species is characterized by a high antioxidant capacity, where, its leaves are an important source of flavonoids, tannins, phenolic compounds, and natural pigments. The extracts of its aerial parts of this species showed the presence of terpineol, known for its significant antimicrobial activity (Ansari et al, 2012) besides its ability to inhibit mycelial growth (Barra et al, 2007). This survey also showed that Punica granatum, Quercus ilex, and Lavandula stoechas were frequently used for the treatment of diseases of the digestive system and are very effective remedies for colon disorders, ulcers, and stomach aches.…”
Section: Resultsmentioning
confidence: 75%
“…According to several studies (Longo et al, 2007;Dahmoune et al, 2014), this species is characterized by a high antioxidant capacity, where, its leaves are an important source of flavonoids, tannins, phenolic compounds, and natural pigments. The extracts of its aerial parts of this species showed the presence of terpineol, known for its significant antimicrobial activity (Ansari et al, 2012) besides its ability to inhibit mycelial growth (Barra et al, 2007). This survey also showed that Punica granatum, Quercus ilex, and Lavandula stoechas were frequently used for the treatment of diseases of the digestive system and are very effective remedies for colon disorders, ulcers, and stomach aches.…”
Section: Resultsmentioning
confidence: 75%